Evaluation of Parameters Affecting Lifting Capacity in Directional Wells for Garraf Oil Field - Kattami , Nawar Qasim; Hadi, Hassan Abdul (Iraqi Journal of Science, 2022)
The cutting transport problem in the drilling operation is very complex because many parameters impact the process, which is nonlinearity interconnected. It is an important factor affecting time, cost and quality of the deviated and horizontal well. The main objective is to evaluate the influence of main drilling Parameters, rheological properties and cuttings that characterise lifting capacity through calculating the minimum flow rate required and cutting bed height and investigate these factors and how they influenced stuck pipe problems in deviated wells for Garraf oil field. The results obtained from simulations using Well Plan™ Software were showed that increasing viscosity depends on other conditions for an increase or decrease fluid flow rate required, increasing cutting density, cutting size, and ROP requires an increased fluid flow rate and when increasing RPM, increasing mud weight reduces the fluid flow rate required hence better hole cleaning. The major findings from the analysis parameter that wellbore inclination, mud density and pipe rotation affect the minimum flow rate needed for good hole cleaning. The drilling section of a well with fluid rates below the minimum flow rate required is considered the major cause of mechanical stuck pipes. In sliding drilling mode, the flow must be increased above the critical flow rate to reduce the likelihood of mechanical stuck pipe. Also, cuttings properties, fluid rheology, and rate of penetration have some influence on cuttings transport.